2015
DOI: 10.1038/pr.2015.132
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated innate immune defenses in very premature neonates during the neonatal period

Abstract: Background: Antimicrobial responses have been shown to be profoundly attenuated in very preterm neonates when examined on cord blood. However, we lack data on these responses at the time these neonates are most vulnerable to infections. Methods: Multiple cytokine responses to two prototypic Toll-like receptor (TLR) agonists: lipopolysaccharide (LPS) (TLR4) and R848 (TLR7/8) were prospectively measured in preterm neonates born ≤30 wk of gestation (n = 50) during the first 28 d of age using whole blood and singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
3
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 27 publications
2
43
3
1
Order By: Relevance
“…Indeed, using both whole blood and single-cell flow cytometry analyses, Marchant et al have confirmed that PRR responses (e.g. TLR4, TLR7/8), remain attenuated in post-natal blood obtained from neonates born below 30 weeks of gestation [95]. These results provide important support to the premise that reduced immune activity is responsible for the high vulnerability to infections.…”
Section: Mechanisms Of Immune Cell Maturation and Function During Ontmentioning
confidence: 83%
“…Indeed, using both whole blood and single-cell flow cytometry analyses, Marchant et al have confirmed that PRR responses (e.g. TLR4, TLR7/8), remain attenuated in post-natal blood obtained from neonates born below 30 weeks of gestation [95]. These results provide important support to the premise that reduced immune activity is responsible for the high vulnerability to infections.…”
Section: Mechanisms Of Immune Cell Maturation and Function During Ontmentioning
confidence: 83%
“…LPS is a Toll-like receptor 4 (TLR4) ligand. Interleukin-6 (IL-6), IL-1β and tumour necrosis factor-α (TNF-α) were measured in triplicate using commercially available ELISA kits (methods previously described [19]). For basal cytokine measurements, high-sensitivity ELISA assays were used (eBioscience, San Diego, Calif., USA).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the levels of antigen specific immunoglobulins are substantially reduced in preterm infants, since these antibodies are largely transferred across the placenta during the third trimester, particularly after the 32nd week of gestation [23]. Preterm birth is also associated with limited production and function of antimicrobial proteins, peptidases and soluble cytokines [22,24,25]. …”
Section: Preterm Birth and Bronchopulmonary Dysplasia: An Immature Symentioning
confidence: 99%